Vertical Differentiaiton, Trade and Endogenous Common Standards - Luca Lambertini; Gianpaolo Rossini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1996)
Different market settings are considered in a free trade environment, where firms can choose technology, quality, and price or quantity. The shape of competition in prices requires the intervention of governments, via a common antidumping policy, to make firms converge on the simultaneous equilibrium which is socially optimal. In the Cournot framework, the equilibria we obtain impinge upon the kind of precommitments undertaken by firms. The coincidence between firms' behaviour and social preference obtains either when competition is tough, since income is low, or when firms must compete in quantities in the market stage, since they cannot modify qualities. The spontaneous coordination over common standards has to be contrasted with both the case of affuent consumers and Bertrand competition.
Keywords: 330